Platinum Electrodes for Oxygen Reduction Catalysis Designed by Ultrashort Pulse Laser Structuring. Issue 3 (2nd February 2017) - Lange, Karsten; Schulz‐Ruhtenberg, Malte; Caro, Jürgen
Abstract: Compact platinum plates have been micro‐ and nanostructured by using a one‐step process with ultrashort laser pulses. Depending on the parameters of the laser treatment (power, line distance, and scan speed), distinct surface structures can be produced by different spot energy densities. The platinum plates structured this way were tested for their electrochemical activity in the oxygen reduction reaction in aqueous HClO4 by using cyclic voltammetry and rotating disk electrode approaches. The laser‐induced surface structuring yields a substantial enhancement in the electrochemical activity of platinum surfaces. The observed rise of the electrochemical activity by a factor of 1500 is attributed to the considerable increase of the surface area. Abstract : Laser cats : The catalytic properties of different laser‐induced surface structures are investigated for the first time by using platinum plates as the electrode material. Different parameters for picosecond laser structuring of platinum are identified, and their effect on the electrochemical properties are discussed.